PHONOSEMANTISM AS PART OF THE SIGN SYSTEM OF LANGUAGE - Andriiva S. S. (International Journal of Innovative Technologies in Social Science, 2021)
Phonosemantics is a science with a thousand-year history, the attitude to which is ambiguous. Despite the fact that the main principle of this linguistic discipline about the motivation of the sound unit and the legitimacy of the phenomenon has been repeatedly questioned, although discussions on the universality and specificity of the phenomenon under study continue to this day. Language is the most powerful means of forming thought; social phenomenon that attest to such its main functions as informational, communicative, emotional, cognitive, epistemological, accumulative. All functions are usually implemented not in isolation, but in various combinations, because each statement in most cases is multifunctional. All functions ultimately work for communication, and that's in the sense that the communicative function is leading. Simultaneously with the acquisition of human language, it acquires knowledge about the world around, which significantly shortens and simplifies the path of cognition, protects a person from unnecessary mistakes. F. de Saussure explained the problem of the value of a linguistic sign, arguing that a linguistic sign combines a concept and an acoustic image and has two essential features: arbitrariness (unmotivated) and linearity (unfolding in time and one dimension). The sign is used to indicate an object outside it, to receive, store and transmit information. A sign acquires its meaning only in a certain system, because outside it is not a sign and means nothing. The palette of phonosemantic searches is inexhaustible, as each linguistic and literary-artistic direction in various manifestations considers the symbolism of images of phonemes, phonemes, morphemes, tokens, syntagms, texts. The scope of using linguistic units with existing phonosemantic features is different types of movement, sound, light phenomena, physiological and emotional states of both humans and animals.